2020
DOI: 10.1111/bph.15279
|View full text |Cite
|
Sign up to set email alerts
|

NH‐sulfoximine: A novel pharmacological inhibitor of the mitochondrial F1Fo‐ATPase, which suppresses viability of cancerous cells

Abstract: Background and Purpose: The mitochondrial F 1 F o-ATPsynthase is pivotal for cellular homeostasis. When respiration is perturbed, its mode of action everts becoming an F 1 F o-ATPase and therefore consuming rather producing ATP. Such a reversion is an obvious target for pharmacological intervention to counteract pathologies. Despite this, tools to selectively inhibit the phases of ATP hydrolysis without affecting the production of ATP remain scarce. Here, we report on a newly synthesised chemical, the NH-sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The sulfoximine compounds are profoundly known for their anti-cancer activity. It has been reported that adenylated sulfoximine is ASNS inhibitors and adenylated sulfoximine 7b has been used to define the enzymes inhibition activity in MOT4 cell lines [ 37 ]. Sulfoximine adenylate was used to dock with the C -terminal region of human ASNS.…”
Section: Discussionmentioning
confidence: 99%
“…The sulfoximine compounds are profoundly known for their anti-cancer activity. It has been reported that adenylated sulfoximine is ASNS inhibitors and adenylated sulfoximine 7b has been used to define the enzymes inhibition activity in MOT4 cell lines [ 37 ]. Sulfoximine adenylate was used to dock with the C -terminal region of human ASNS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IF1 acts as a novel clinical biomarker of dermatomyositis and a potential metabolic driver of cancer incidence ( 61 ). Novel pharmacological inhibitors of IF1 are developed to counteract pathologies ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present work underscores a central role of mitochondria in pathological growth responses in the heart and supports current efforts to design mitochondrial targeted therapies for HF [ 34 , 35 , 36 , 37 ]. IF1 appears to be both an attractive and feasible target for pharmacological modulation as several compounds are currently in various stages of clinical development [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%